UHPC grout-filled pipe sleeve with bolts for large-diameter deformed bars: Analytical model on the tensile resistance and design method. (15th October 2021) - Wang, Zhen; Zhu, Junzheng; Wang, Jingquan; Zhao, Guotang; Sun, Shuli; Zhang, Jian
Highlights: A novel UHPC grout-filled pipe sleeve with bolts is proposed for large-diameter deformed bars. An analytical model is established for predicting the tensile resistance of the pipe sleeve. The bar-grout interface is studied considering the friction, ribs against grout, and pipe's confinement. The grout-pipe interface resistance is from the interface bond and contribution of bolts. A developed design method can give a pipe sleeve scheme with an embedded length of 6 db  ~ 7 db . Abstract: A novel UHPC grout-filled pipe sleeve with bolts was put forward for connecting large-diameter deformed bars and its feasibility was experimentally verified in a previous study. But it is not easy to rapidly broaden its application partly due to the lack of relevant calculation and design knowledge. This study aims to establish an analytical model on the tensile resistance that is dependent on the deformed bar-UHPC grout and UHPC grout-steel pipe interfaces, and develop a design method for the proposed pipe sleeve. In the model, the former interface resistance was analytically calculated considering the friction resistance, bearing of ribs against UHPC grout, and steel pipe's confinement. A dimensionless index ηb-g was defined to measure the relationship of the bond stress and pressure at the interface, and calibrated based on the experimental results. The latter interface resistance was analytically calculated considering the interface bond strength and resistance of bolts. Experimental results were adopted to verify the analytical model. A design method was developed for the pipe sleeve based on the verified analytical model, and a design case was given to illustrate how to use it. Results show that the analytical model can accurately predict the two interface resistances. ηb-g is respectively recommended for three categories of pipe sleeves, that are distinguished by the existence of bolts and grout type. The design method is convenient to provide a feasible design scheme of the pipe sleeve for a specified large-diameter deformed bar, of which the embedded length can be reduced to be 6 ~ 7 times bar diameter.